Modernity and Muslims: Toward a Selective Retrieval (American Journal of Islam and Society, 2011)
This article is focused on some conditions in today’s world of globalized media, which are producing either an uncritical acquiescence or fright in Muslim societies as a result of the interaction between these societies and the contemporary Western powers that represent modernity and postmodernity on the global stage. The rise of fundamentalism, a tendency toward returning to the roots and stringently insisting upon some pure and literal interpretation of them, in almost all the religions of the world is a manifestation of this fright. The central concern of this article is to suggest that fundamentalism is neither the only nor the most reasonable response for Muslim societies in the face of contemporary modernity. Muslims need to adopt an independent and critical attitude toward modernity and reshape their societies in the light of the ethics of the Qur’an, keeping in view the historical link between Islam and science in as much as Islamic culture paved the way for emergence of modern science during European Renaissance. The necessity of a pluralistic or contextualized modernization of Muslim societies is discussed along with the need for the removal of cultural duplicity in the role of the West in relation to Muslim societies. All this leads to an overall proposal for modernization which is given towards the end.